2020
DOI: 10.3390/rs12142286
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Distribution of PM2.5 Pollution over Northeastern Mexico: Application of MERRA-2 Reanalysis Datasets

Abstract: Aerosol and meteorological remote sensing data could be used to assess the distribution of urban and regional fine particulate matter (PM2.5), especially in locations where there are few or no ground-based observations, such as Latin America. The objective of this study is to evaluate the ability of Modern-Era Retrospective Analysis for Research and Application, version 2 (MERRA-2) aerosol components to represent PM2.5 ground concentrations and to develop and validate an ensemble neural network (ENN) model tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…The investigation of spatial differences and temporal variation patterns is an important part of the research on air pollution [8]. A study found higher levels of PM 2.5 concentrations in Mexico in winter and spring using the MERRA-2 reanalysis datasets, with the highest concentrations occurring in spring [9]. Fine particulate matter in the United States has shown a decreasing trend over time in recent decades [10].…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of spatial differences and temporal variation patterns is an important part of the research on air pollution [8]. A study found higher levels of PM 2.5 concentrations in Mexico in winter and spring using the MERRA-2 reanalysis datasets, with the highest concentrations occurring in spring [9]. Fine particulate matter in the United States has shown a decreasing trend over time in recent decades [10].…”
Section: Introductionmentioning
confidence: 99%
“…In northeastern Mexico, only Carmona et al (2020) [17] has evaluated the ability of MERRA-2 aerosol components to represent PM 2.5 ground concentrations and to develop and validate an ENN model to estimate monthly average PM 2.5 ground concentrations. The results of their comparison between the ENN and ground measurements were as follows: R =~0.90, RMSE = 1.81 µg m −3 , and MAE = 1.31 µg m −3 .…”
Section: Contributions In the Context Of Latin Americamentioning
confidence: 99%
“…The AOD-PM 2.5 relationship, however, varies in space and time and needs to be specifically assessed for different regions and seasons [15]. Despite Latin America being one of the most urbanized, populated, and polluted regions in the world, where most cities lack robust ground-based PM 2.5 monitoring networks, few studies have examined the relationship between AOD and PM 2.5 in this region (e.g., [16][17][18][19][20]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MERRA-2 data has been found to better simulate surface fine particulate mass PM 2.5 [47]. Some studies have shown the compatibility of MERRA's data trends with ground trends, such as the study conducted in the Monterrey Metropolitan Area in Mexico [48].…”
Section: Modern-era Retrospective Analysis For Research and Applications Version 2 (Merra-2)mentioning
confidence: 99%